Quality of follow-up care for premature infants in primary health care: A cross-sectional study from nurses' perspective in Paraná state, Brazil - Ivaneliza Simionato de Assis; Geisyelli Alderete; Regiane Bezerra Campos; Marcos Augusto Moraes Arcoverde; Debora Falleiros de Mello; Adriana Zilly; Rosane Meire Munhak Silva (PLoS ONE, 2026)
Background Prematurity affects approximately 10% of births worldwide and represents the leading cause of mortality in children under five years of age. The considerable variability in follow-up programs for premature infants internationally indicates the need for standardized protocols. In Brazil, the discontinuity of follow-up care for children after hospital discharge constitutes a significant weakness, particularly in regions with socioeconomic disparities. Despite the essential role of Primary Health Care, there are gaps in evaluating the quality of follow-up care for premature infants from the perspective of health professionals, particularly nurses. This study aimed to the perceived quality of follow-up care for premature children in Primary Health Care from the perspective of nurses working in Paraná state, Brazil. Methods Cross-sectional, descriptive, and analytical study with a quantitative approach, conducted with 463 nurses working in Primary Health Care between 2024 and 2025 in Brazil. The “Qualipreterm” instrument was used to evaluate five quality domains: hospital discharge planning, home follow-up, child health follow-up, integration between services, and family support. Descriptive analyses, chi-square tests, and spatial distribution description through thematic maps were performed. Results From the nurses’ perspective, Domain I (hospital discharge planning) showed 58.9% of evaluations classified as inadequate. Domain V (family support) demonstrated the best performance, with 58.5% of evaluations classified as good and 3.5% as excellent. Domains II, III, and IV showed a predominance of regular classification (56.4% to 59.8%). Regional analysis revealed heterogeneity among the macro-regions studied, with some showing greater consistency in quality while others faced greater challenges in hospital discharge planning. Conclusions The study reveals weaknesses in the perceived quality of follow-up care for premature infants in Primary Health Care, from the perspective of nurses, indicating the need for implementation of standardized protocols that promote longitudinal care, increased coordination strategies between healthcare network service points, and strengthening of continuing education for healthcare professionals.